Research progress on the production mechanism and control measures of two chiral lactic acid in Baijiu brewing process - YANG Rong, HUA Jin, ZHOU Yabin (Zhongguo niangzao)
In Baijiu brewing process with open fermentation, lactic acid bacteria were introduced into fermented grains to produce L-lactic acid and D-lactic acid. Lactic acid was distilled into the liquor body, and were important flavor substances in Baijiu. However, excessive lactic acid may affect alcohol metabolism and the comfort of human body after drinking. Different brewing raw materials, lactic acid bacteria and production technologies led to different contents and proportions of two chiral lactic acid in Baijiu, which led to differences in flavor and quality of Baijiu. In this paper, the production mechanism of two chiral lactic acid in Baijiu was reviewed. The metabolic function in human body, the content and proportion difference of two chiral lactic acid in Baijiu were summarized. The effects and control measures of raw materials, Jiuqu, fermented grains, fermentation process, fermentation temperature, L-lactic acid high-yielding strain, distillation technology and pit muds on two chiral lactic acid production were discussed, and the effect of two chiral lactic acid on Baijiu quality was discussed, aiming to provide some references for increasing L-lactic acid and reducing D-lactic acid regulation in Baijiu production without affecting the flavor of Baijiu.